Voluntary Feed Intake and Growth of Local Sheep Fed on Road Side Grasses Following A 6-Week Feed Restriction Period - Yuwono, P; Hartoyo, B; Priyono, A; Soeprapto, H (ANIMAL PRODUCTION, 2000)
The purpose of this experiment was to investigate an adaptation time sheep to eat at a normal amount required by the local experiencing liveweight loss due to feed restriction, to investigate feed intake and feed digestibility and to investigate sheep growth following feed restriction. The experiment was conducted in The Experimental Farm of Faculty of Animal Husbandry, Unsoed. Twelve local sheep were randomly assigned to two different groups of treatment: namely, control (C) and restrictively Fed Animal (R). there were two periods through out the experiment, Period I (PI) and II (PII). During P I (6 week), Animals in group R were restrictively fed so that they lost live weight of approximately 15%. During P II Animals in groupÂ  R were than offered ad libitum. Whereas, animal in group C were fed ad libitum through out the experiment. The results of this experiment showed that animals in group R needed 17 days for adaptation to consume feed at a normal amount after they had experienced feed restriction for 6 weeks. Dry matter intake was not different between group C dan R. However, when it was expressed per metabolic live weight (g/Kg0,75), Dry matter intake for group R was significantly higher than that for group C (102.35 vs 91,79). Dry matter digestibility value for group R was higher than that for group C either during PI (62 vs 57%) or during PII (70 vs 61%). The rate of live weight gain was not different between C and R during period II. In conclusion, local sheep had capability of consuming more feed after resumption of full feeding for 17 days. (Animal Production 2(2): 47-52 (2000)Â Key words : local sheep, dry matter, organic matter, period, restriction, digestibility